Contrast‐enhanced micro‐computed tomography of compartment and time‐dependent changes in femoral cartilage and subchondral plate in a murine model of osteoarthritis. Issue 1 (11th July 2022) - Chan, Deva D.; Mashiatulla, Maleeha; Li, Jun; Ross, Ryan D.; Pendyala, Meghana; Patwa, Amit; Grinstaff, Mark W.; Plaas, Anna; Sumner, D. Rick
Abstract: A lack of understanding of the mechanisms underlying osteoarthritis (OA) progression limits the development of effective long‐term treatments. Quantitatively tracking spatiotemporal patterns of cartilage and bone degeneration is critical for assessment of more appropriately targeted OA therapies. In this study, we use contrast‐enhanced micro‐computed tomography (μCT) to establish a timeline of subchondral plate (SCP) and cartilage changes in the murine femur after destabilization of the medial meniscus (DMM). We performed DMM or sham surgery in 10–12‐week‐old male C57Bl/6J mice. Femora were imaged using μCT after 0, 2, 4, or 8 weeks. Cartilage‐optimized scans were performed after immersion in contrast agent CA4+. Bone mineral density distribution (BMDD), cartilage attenuation, SCP, and cartilage thickness and volume were measured, including lateral and medial femoral condyle and patellar groove compartments. As early as 2 weeks post‐DMM, cartilage thickness significantly increased and cartilage attenuation, SCP volume, and BMDD mean significantly decreased. Trends in cartilage and SCP metrics within each joint compartment reflected those seen in global measurements, and both BMDD and SCP thickness were consistently greater in the lateral and medial condyles than the patellar groove. Sham surgery also resulted in significant changes to SCP and cartilage metrics, highlighting a potential limitation of using surgical models to study tissue morphology or composition changes during OA progression. Contrast‐enhanced μCT analysis is an effective tool to monitor changes in morphology and composition of cartilage, and when combined with bone‐optimized μCT, can be used to assess the progression of degenerative changes after joint injury.